Exploring the Role of AI-based Tools in Enhancing Student Learning Outcomes - Asrani, Lit; Shamsiah, Suhaili; Maimun Huja, Husin; Kuryati, Kipli; Hishammudin Afifi, Huspi; Fariza, Mahyan (2024)
—Beyond chatbots, AI’s application extends to serving as virtual assistants to educators, enhancing their capacity to support student learning in diverse ways. In the context of this study, we delve into the extensive advantages AI tools offer in boosting the learning outcomes of students. Our research specifically targets the effectiveness of AI in elevating the academic performance of first-year undergraduates within the Electrical and Electronics Department at the Faculty of Engineering, Universiti Malaysia Sarawak (UNIMAS). The empirical data from our study presents a compelling argument for AI’s positive influence on educational outcomes. It reveals a consensus among participants that AI not only facilitates easier access to learning materials and enhances understanding but also promotes a sense of independence among learners. Our findings underscore a rising inclination towards adopting tech-driven innovations within the educational sphere of the university. Nonetheless, it also brings to light the critical need for an integrated approach that marries AI technologies with conventional pedagogical techniques, aiming for a curriculum that fosters comprehensive development of students. One of the standout observations from the research is the perceived potential of AI to democratize educational opportunities, suggesting its pivotal role in creating an equitable learning environment that accommodates students from varied backgrounds. Conclusively, the survey highlights a broad endorsement of AI’s role in achieving educational goals, while also stressing the importance of its thoughtful integration to enhance various facets of student growth.